TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

CqSESN2 suppresses WSSV infection via the CqNrf2 antioxidant pathway in Cherax quadricarinatus - Yan Wang; Kai-Ming Cai; Xuan Zeng; Wen-lin Wu; Hai-Peng Liu (Fish & Shellfish Immunology, 2026)

Tailoring lattice confinement and conductivity of AlF co-doped Li2TiO3 ion sieves for highly selective lithium electrosorption - Ruini Zou; Yaxuan Wang; Ming Gao; Yijiao Chang; Bing Li; Xiao-yan Li; Lin Lin (Desalination, 2026)

Overlooked effects of common alcohol quenching agents on electron transfer pathway in persulfate activation system - Xuerong Zhou; Lin Zhang; Shiyu Liu; Huchuan Yan; Dengsheng Ma; Qihong Yang; Bing Ding; Cui Lai; Ming Yan; Zizhu Peng (Chemical Engineering Journal, 2026)

The progressive formation process of the tectono-metamorphic mélange belt: An example from the Mogutai massif, Dunhuang Orogenic Belt, Northwest China - Yichao Chen; Xue-Li Jia; Qian W.L. Zhang; Zhen M.G. Li; Hui C.G. Zhang; Hao Wang; Wenjiao Xiao; Yan-Lin Zhao; Haiquan Tang; Chang-Ming Lu; Chun-Ming Wu (Journal of Structural Geology, 2026)

Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Experimental and numerical research on ultimate bearing capacity of steel-concrete-steel composite deep beams with UHPC/ECC considering interfacial bonding - Youzhu Lin; Yazhe Zou; Ming Sun; Jiachuan Yan (Engineering Structures, 2026)

Piezoresistive AgNPs-MXene/TPU strain sensors with hierarchical microstructures via template-assisted phase separation and in-situ growth for health monitoring and emergency rescue - Guanting Wu; Songyue Pan; Chuanxi Lin; Weijie Wang; Jiatong Yan; Ming Zhong; Hong Tang; Ronghui Guo (Chemical Engineering Journal, 2026)

Electron push-pull engineered Fe-Co dual-atom hollow nanofiber membranes drive super-efficient and sustainable electro-Fenton water purification - Ruiquan Yu; Wutong Chen; Ming Gao; Hao Lin; Chao Yang; Bing Li; Xiao-yan Li; Lin Lin (Water Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Corrigendum to “OsCOPT7 is involved in copper accumulation and transport through xylem” [J Hazard Mater 477 (2024) 135245] - Mei Yan Guan; Zhenzhen Cao; Yu Chun Xia; Ping Xv; Xiao Yan Lin; Ming Xue Chen (Journal of Hazardous Materials, 2026)

Application of short-wave infrared spectroscopy in sandstone-type uranium deposits: A case study of the Yuejin-II uranium deposit in the Qaidam Basin, China - Wen-Yi Wu; Ming-Sen Fan; Pei Ni; Jun-Yi Pan; Yi-Han Lin; Yan Zhou; Chen Zhang; Ruo-Yu Shi; Xue-Feng Gao; Duo Wang; Bin Guo; Xiao-Qin Xu; et al. (Journal of Geochemical Exploration, 2026)

Bioremediation of α-terpineol-contaminated flotation wastewater using biochar-immobilized biosurfactant-producing bacteria - Jin-Cheng Ye; Ying-Xi Liu; Huan Du; You-Qun Xie; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Environmental Management, 2026)

Corrigendum to Avermectin induces developmental toxicity and immunotoxicity in zebrafish larvae. Journal of Environmental Sciences (2026), doi: https://doi.org/10.1016/j.jes.2026.03.02 - Wei-Guo Wang; Shou-Lin Li; Da-Wei Yan; Yun-Fei Sha; Wen-Ping Xu; Jia-Gao Cheng; Zhong Li; Li-Ming Tao; Yang Zhang (Journal of Environmental Sciences, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Metamorphic evolution and geochronology of garnet amphibolite, the Dongbatu tectonic-metamorphic mélange, eastern middle Paleozoic Dunhuang Orogenic Belt, northwest China - Xue-Li Jia; Yichao Chen; Yan-Lin Zhao; Zhen M.G. Li; Hui C.G. Zhang; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Short anti-aging peptides from edible microalgae using a multi-targets virtual screening strategy combined with Caenorhabditis elegans model - Yan-yan Yuan; Xin Li; Ming-hui Han; Xue An; Yong-Qiang Lin; Hong-Bing Liu (Food Research International, 2026)

Iron oxide catalytic pyrolysis and iron oxide-steam catalytic gasification of epoxy resin: Mechanistic insights from experiments, ReaxFF MD and DFT - Meng Sun; Hongxin Liang; Zhen Wang; Jianbiao Chen; Yan Shang; Ming Dong; Liang Wang; Lin Mu (Chemical Engineering Journal, 2026)

Revealing the kinetic promotion mechanism of carbon nanotubes to methane hydrate formation: As to the situation coupled with traditional kinetic promoter L-leucine - Yan Lin; Yan-Ling Guo; Zhi-Yuan Wang; Jie Zhong; Xiao-Ming Wang; Yi-Ning Ding; Hong-Zheng Lu; Fei Wang; Xiao-Lin Wang (Chemical Engineering Journal, 2026)

Phage-Display Identification of Urate-Binding Cyclic Peptides with Preliminary Urate-Lowering Activity in Adenine-Induced Hyperuricemic Rats - Mi Ai; Zhi-Ming Wang; Wei-Lin Guo; Xue-Qi Li; Li-Ting Xiao; Yan-Shan Mai; Hong-Bin Zhang (International Journal of Peptide Research and Therapeutics, 2026)

Bacillus subtilis modulates the intestinal microbiome and metabolism to promote growth and disease resistance in Micropterus salmoides - Meiyu Li; Wengen Zhu; Shuhui Niu; Xingxing An; Lin Chen; Houxiong He; Yaohua Wang; Song Zhang; Yong Yang; Qirui Li; Huanping Liu; Shuhan Zhang; et al. (Aquaculture, 2026)

TomOmics: An integrative multi-omics platform for comparative and functional research in tomato - Yan Wang; Tailai Yang; Yuru Song; Qinqin Yang; Xiao Su; Hongwei Li; Yushan Li; Ming Zhou; Tao Lin (Molecular Plant, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

Genetic regulation of insulin resistance surrogate index (TyG) and susceptibility to common diseases based on phenome-wide association study - Jia-Xin Wu; Ling-Huan Bu; Pei He; Ming-Hui Xia; Lin Bo; Fei-Yan Deng; Shu-Feng Lei (Molecular and Cellular Biochemistry, 2026)

Impact of habitat biotic factors on selective food hoarding in Brandt's voles - Shan-shan Sun; Tao Liu; Hai-rui Yang; Zhi-liang Zhang; Ya-nan Li; Ming Ming; Hao-ting Zhang; Hai-wen Yan; Xin Li; Lin-lin Li; Na Zhu; Xiao-dong Wu; et al. (Journal of Arid Environments, 2026)

A high-performance bimodal sub-nanoporous polyelectrolyte complex membrane for organic solvent nanofiltration constructed by MOF-reinforced nano-unit - Hui-Qian Huo; Bing-Xin Gu; Jin-Lin Wang; Jia-Chen Zhang; Kai Zhang; Ming-Jie Yin; Yan-Li Ji; Quan-Fu An (Chemical Engineering Journal, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

Preparation of cancer cell membrane-coated Gambogic acid-loaded pH-sensitive liposomes to enhance targeted anti-hepatocellular carcinoma effect - Yi-Feng Zhang; Kun Chen; Yu-Qing Zhu; Lin Liu; Xiang-Tao Kong; Yan Dai; Xiu-Juan Fu; Ya-Ling Li; Ming-Hua Liu; Dan Zhang (Drug Delivery and Translational Research, 2026)

Chronology and geochemistry of radiolarian chert from Zhongba, southern Xizang (Tibet): Implications for the evolution of the Neo-Tethys Ocean - Han Yan; Han-Ting Zhong; Zong-Qi Lin; Chen-Yu Wang; Ling-Xue Gao; Cai Wang; Ming-Cai Hou (Palaeoworld, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Chlorine-resistant high-entropy spinel oxide catalyst for efficient and durable seawater anion exchange membrane water electrolysis - Thi Xuyen Nguyen; Ting-You Shih; Ngoc Thanh Thuy Tran; Thanh Tuan Nguyen; Yi-Chuan Chu; Bo-Han Lai; Chun-Kuo Peng; Yu-Ru Lin; Yan-Gu Lin; Kao-Shu Chuang; Jeng-Kuei Chang; Thi Y Phung Nguyen; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal relationships between mammal habitat suitability and recreational hiking intensity in Xiaowutaishan National Nature Reserve, China - Ming Yam Chan; Yue Cao; Zhicong Zhao; Pei Wang; Yunshuang Feng; Le Yu; Steve Carver; Xuehua Liu; Ruijia Zhu; Fengze Lin; Xialin Li; Yiqing Wang; et al. (Biological Conservation, 2026)

Coupled Effects of Reservoir Level Fluctuations and Rainfall on Landslide Deformation Using InSAR and DEM Analysis - Liu Tie-biao; Liu Ming-quan; Luo Shi-lin; He Kun-lin; Yan Guang-zhi; Chen Guo-feng; Cao Su-ting (Geotechnical and Geological Engineering, 2026)

Diverse metamorphic P‒T‒t paths of the Mogutai tectono-metamorphic mélange, eastern Paleozoic Dunhuang Orogenic Belt, northwestern China - Yan-Lin Zhao; Yichao Chen; Xue-Li Jia; Hui C.G. Zhang; Zhen M.G. Li; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Can karst aquifer for public supply threatened by lead smelting be sustainably managed? Part I: Evidence from lead isotopes - Bei-Yi Xu; Run-Zhi Xie; Song-Lin Liu; Jian-Ming Zhu; Wu-Tian Cai; Yan Zheng (Geochimica et Cosmochimica Acta, 2026)

Microencapsulation mechanism of menthol and menthone by hydroxypropyl-β-cyclodextrin for enhanced stability and prolonged retention - Honghui Guo; Haohong Yao; Quanxing Zheng; Quanling Xie; Hongliang Lu; Xiaohua Deng; Yan Lin; Ming’en Zhang; Pengfei Ma; Zhuan Hong; Xiaoqing Huang (Food and Bioproducts Processing, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

Cytoplasmic-nuclear remote suppression of c-MYC induces cell cycle arrest and enhances radiotherapy sensitivity in liver cancer via biohybrid platelets - Lin Xiao; Fei Ge; Qinyu Ji; Rui Ji; Yan Wang; Shaoqing Ju; Ming Cui; Donglin Xia; Rongrong Jing (Chemical Engineering Journal, 2026)

Sublethal exposure to an amitraz-fluvalinate-coumaphos mixture disrupts honeybee gut microbiota and sensitizes to neonicotinoid toxicity - Kang Wang; Jinmeng Ma; Ming Zheng; Yuanchan Fan; Yi Zhang; Wenan Zhang; Yan Zhang; Zheguang Lin; Ting Ji (Environmental Research, 2026)

Risk classification and zoning management of heavy metal pollution in paddy soils: A model coupling soil health and source apportionment - Ying Luo; Zhe Wang; Jia-qian Zhang; Chao-liang Peng; Kai Ye; Zhen-long Zhang; Wen-xue Lin; Jing-yan Zhang; Yi-ming Chen; Wei-hao Wang; Jia-xin Liu; Duan Tian; et al. (Environmental Research, 2026)

Peak load prediction and interface behavior analysis of steel–ECC composite slabs: Experiments, simulations and theoretical models - Youzhu Lin; Haijun Wang; Ming Sun; Yuanbo Hu; Di Yao; Jiachuan Yan (Engineering Structures, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

A review on integrated isotopic and receptor model approaches for urban REE source appointment - Muhammad Ubaid Ali; Muhammad Adnan; Xiao Yan Lin; Sajid Ali; Zhuanxi Luo; Yu Yan; Gongren Hu; Ruilian Yu; Ming Hung Wong (Environmental Geochemistry and Health, 2026)

Simple characterization of compression–adhesion behavior of foam–conditioned soil in EPB shield tunneling - Ming Huang; Chengzhi Lin; Yao Lu; Chaoxian Wang; Shuaixing Yan; Guangyuan Cai (Tunnelling and Underground Space Technology, 2026)

Ripened Pu-erh tea modulates the gut microbiome to enhance metabolic homeostasis and redox-inflammatory balance: A systematic review of core health benefits and mechanisms - Ming Zhao; Teng Wang; Lin Zeng; Qiuyue Chen; Dihan Yang; Yiqing Guan; Nianguo Bo; Yong-Quan Xu; Yan Ma (Trends in Food Science & Technology, 2026)

ER stress disrupts MFN2-related mitophagy via HRD1-PINK1/ parkin axis in bovine embryos - Shu-Ming Shi; Li-Ying Liu; Zhi-Chao Chi; Lin-Yi Qu; Jing-Hang Li; Guan-Lin Jia; Yu-Yan He; Yong-Xun Jin; Ming-Jun Zhang; Xian-Feng Yu (Theriogenology, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

ROS responsive polydopamine coated black phosphorus nanocarrier for enhanced methylprednisolone delivery in acute lung injury immunotherapy - Zhiwei Gao; Mengxue Mo; Qianyue Liu; Jiaxiao Li; Hongshuai Zheng; Yaohui Huang; Yan Liu; Jing Qian; Xuzhi Liang; Yuting Xiao; Yan Long; Chen Qian; et al. (Chemical Engineering Journal, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Labdane-type diterpenoids from Hypoestes phyllostachya inhibit pancreatic cancer stem cells - Tong Yan; Lin-Fen Ding; Ya Chen; Guo-Xian Hu; Lu Qu; Ming Hu; Ya-Xuan Ma; Rong-Qing Yuan; Lin Jia; Mei-Ju Zhao; Liu-Dong Song; Jia Su; et al. (Phytochemistry, 2025)

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Molecular interactions between natural pungent spices and grass carp myofibrillar protein: Conformational remodeling deciphered through multiscale characterization - Yuan Tang; Xiaojuan Lei; Yan Liu; Mengcong Liu; Lin Lei; Kaihong Zeng; Jian Ming (Food Research International, 2025)

Experimental study and theoretical analysis on ultimate bearing capacity of steel-concrete-steel deep beams with UHPC after freeze-thaw cycles - Youzhu Lin; Chuanbo Yu; Ming Sun; Xinya Mao; Pengxi Jia; Jiachuan Yan (Engineering Structures, 2025)

Source identification and source-oriented human health risk assessment of heavy metal pollution in soil - dustfall - crop around non-ferrous metal smelting slag yards - Ying Luo; Zhe Wang; Kai Ye; Jia-qian Zhang; Chao-Liang Peng; Zhen-long Zhang; Wen-xue Lin; Jing-yan Zhang; Yi-ming Chen; Ling Hu (Journal of Soils and Sediments, 2025)

Serum cortisol and AdipoR2 rs12342 were involved in the correlation between stress and serum cholesterol in a gender-specific manner - Yi Lin Shen; Qi Wei Guo; Xue Cheng Li; Ke Xin Jia; Jun Yi Liu; Yan Zhi Yi; Jun Tao Ren; Jia Jing Cai; Guo Ming Su; Jia Lin; Ding Zhi Fang (Metabolic Brain Disease, 2025)

Enhanced bioremediation of α-terpineol-contaminated mining soil through immobilization of Indigenous biosurfactant-producing bacteria on biochar - Jin-Cheng Ye; Wei-Liang Li; You-Qun Xie; Huan Du; Lei Xiang; Bai-Lin Liu; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Miaoyue Zhang; Ce-Hui Mo; Hai-Ming Zhao (Biology and Fertility of Soils, 2025)

Overlooked synergisms of flotation organic reagents and toxic metals in water: Formation of tridentate cadmium-xanthate complexes - Lei Xiang; Qian-Wen Wang; Wen-Jun Wu; Nian-Jue Zheng; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; Qing X. Li (Water Research, 2025)

Salidroside improves bovine embryo quality by mitigating oxidative stress and regulating mitochondrial lipid metabolism - Li-Ying Liu; Xian-Feng Yu; Zhi-Chao Chi; Shu-Ming Shi; Tian Lan; Jia-Hui Leng; Jing-hang Li; Yu-Yan He; Lin-Yi Qu; Guan-Lin Jia; Ilkeun Kong; Ming-Jun Zhang; et al. (Theriogenology, 2025)

Structural insight into GPR155-mediated cholesterol sensing and signal transduction - Delin Li; Xiaokang Zhang; Jie Feng; Yufeng Xie; Pu Han; Ming He; Lin Hao; Tianling Guo; Xiaoyi Bai; Kai Yuan; Junqing Sun; Xuefei Pang; et al. (Science Bulletin, 2025)

Geology, isotope geochemistry and geochronology of the quartz vein-type Pb–Zn deposits in southeastern Guizhou province, SW China - Hao-Ming Deng; Yong-Yong Tang; Ya-Jiang Tian; Lin Du; Ming-Hong Zheng; Zhi-Qiang Yan; Jia-Xi Zhou; Lin Ye (Journal of Asian Earth Sciences, 2025)

Experimental study, finite element simulation and theoretical analysis on punching shear capacity of steel-ECC composite slabs - Youzhu Lin; Di Yao; Ge Gao; Tianfei Gu; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

Ultimate strength of bamboo scrimber-concrete composite beams with UHPC and ECC: Experimental investigation, finite element simulation and prediction model - Mengqi Cao; Youzhu Lin; Ming Sun; Jiachuan Yan (Engineering Structures, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Predicting joint loading in Asian overweight and obese females with flexible flatfoot: a regression analysis of anthropometric parameters and gait dynamics - Linjuan Wei; Guoxin Zhang; Tony Lin-Wei Chen; Yan Wang; Yinghu Peng; Ming Zhang (Medical & Biological Engineering & Computing, 2025)
Current methods for obtaining accurate joint loading data lack simplicity, efficiency, and cost-effectiveness. This study aims to generate joint loading prediction models using anthropometric parameters and walking speed in overweight or obese females with flexible flatfoot. Sixteen participants’ motion capture data from walking trails and anthropometric parameters were collected. The lower limb joint contact forces and the walking speed were calculated via a musculoskeletal model. Regression analysis was used to generate the prediction model. The second peak of knee joint contact force revealed a strong negative correlation with hip circumference and a weak positive correlation with age ( p < 0.001 and adjusted R 2 = 0.720). The peak ankle joint contact force exhibited a strong positive correlation with walking speed while strong negative correlations with waist circumference and lower limb length ( p < 0.001 and adjusted R 2 = 0.782). The first peak of vertical GRF displayed a medium negative correlation with walking speed ( p < 0.001 and adjusted R 2 = 0.750). Anthropometric parameters and walking speed are effective predictors of joint loading. This rapid, low-cost estimation method can be applied to areas such as flexible flatfoot that require assessment of joint stress, thereby saving costs and time. Graphical abstract

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

Quantitative inversion of soil heavy metal pollution using a GA-BP neural network model - Yi-ming Chen; Zhe Wang; Chao-liang Peng; Ying Luo; Jia-Qian Zhang; Zhen-Long Zhang; Kai Ye; Wen-xue Lin; Jing-yan Zhang; Duan Tian; Wei-hao Wang (Environmental Monitoring and Assessment, 2025)

Research on the calculation methods for time-domain friction excitation force in mixed lubrication contact between ship shaft and bearings - Chang-Gang Lin; Hao Wang; Can Sima; Yan-Feng Han; Wei-peng Zhang; Ming-Song Zou (Ocean Engineering, 2025)

Optimization of water intake systems: Based on water-carbon relationships and sustainable development goals - Shixiong Du; Huaiwei Sun; Baowei Yan; Changmei Liang; Siyue Li; Yuanyao Ye; Ming Ye; Lin Chen; Wenxin Zhang (Journal of Hydrology, 2025)

Simulation and prediction of vertical migration of Cd²⁺ in heavy metal-contaminated soils amended with different passivators via Hydrus-1D - Ying Luo; Zhe Wang; Cheng-xia Wang; Jia-Qian Zhang; Kai Ye; Chao-liang Peng; Yi-ming Chen; Zhen-Long Zhang; Wen-xue Lin; Jing-yan Zhang; Shao-qin Chen (Journal of Environmental Chemical Engineering, 2025)

One-step baking soda activation induces N, S-self-doped Ginkgo biloba-derived carbon for efficient chlorine removal - Jiaxi Wang; Limei Sun; Shuaishuai Zhang; Yao Zhang; Ran Zhang; Lin Tian; Yan Xu; Ming Song; Wenchang Zhuang; Wenyi Tan (Journal of Environmental Chemical Engineering, 2025)

Synergistic performance of FeWO4-WO3 composite for enhanced electrocatalytic detection of azathioprine in biological and environmental samples - Anupriya Jeyaraman; Ruey-Shin Juang; Shen-Ming Chen; Zih-Hao Lin; Yan-Chen Hsiang; Ming-Sheng Chen (Journal of Environmental Chemical Engineering, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Green antibiotic breakthrough: Short–rotation woody crops pulp waste liquor defeats drug-resistant bacterial biofilms - Yan Lin; Ting Jiao; Jian Jiao; Ming Zhang; Wentao Wang (Chemical Engineering Journal, 2025)

Assessment of true laterites for their use as liners in karst-depression tailings impoundments - Hai-Yan Gao; Jia-Ming Zhang; Ji-Pu Chen; Lin Tian; Kun Wang; Ze-Min Xu (Bulletin of Engineering Geology and the Environment, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Geological Structural Characteristics of Subashi in West Kunlun Revealed by Aero Geophysical and Remote Sensing Data - Ming Wang; Yi-chuan Li; Hai-qing Wang; Yan-yan Wei; Xiao-xing Lin; Dao-qing Zhou; Jin-zhong Yang; Chang Zhong; Chang-chun Yu (Applied Geophysics, 2025)

Perfluorooctane sulfonate (PFOS) promotes transformational transfer of antibiotic resistance genes and cross-resistance between antibiotics and PFOS - Hui Zhao; Hai-Ming Zhao; Feng Wu; Bai-Lin Liu; Hui Li; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; Ce Hui Mo; Qing X. Li (Water Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Synergistic separation of imprinted composite membranes: Combining a porous graphene oxide skeleton with continuous MOFs nanolayers for superior selective separation - Yilin Wu; Hang Cui; Jiaqing Zhang; Chao Zhou; Rongxin Lin; Zequan Diao; Ming Yan (Desalination, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

Seismic scattered wave direct imaging in shallow underground space with undulating surface - Ke Shi; Feng Xu; Zong-ling Yan; He-jun Chai; Xue-ming Jia; Xing-lin Lu; Xian-xin Liu; You-ping Mao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Localized Trefftz method for wave generation and propagation in a two-dimensional numerical wave tank - Xiran Lin; Liangbin Xu; Yan-Cheng Liu; Chia-Ming Fan (Ocean Engineering, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

Dual-PROTACs based on natural product derivative potassium dehydrographolide succinate: design, synthesis, and antitumor activity of a novel EGFR degrader - Ruling Shi; Peixi Zhang; Ming Chen; Weiming Lu; Meng Xu; Huagong Zeng; Jie He; Yan Wang; Yirong Lin; Jieqing Liu (Medicinal Chemistry Research, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Industrial air pollution and newborn hearing screening failure - Yanhong Huang; Yan Lin; Roberta P. Lavin; Li Luo; Ming Luo; Shuguang Leng; Netanya M. Mullen; Karen Hawley; Xi Gong (Journal of Hazardous Materials, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Tailoring Cu3Nx clusters on TiO2 nanosheets to the sub-nanometric scale for enhancing NH3 photosynthesis - Hyun Sik Moon; Yu-Jeong Yang; Getasew Mulualem Zewdie; Geon Youn; Yi-An Chen; Yu-Peng Chang; Kai-Chi Hsiao; Ting-Han Lin; Yi-Dong Lin; Jun Kue Park; Jucheol Park; Yan-Gu Lin; et al. (Chemical Engineering Journal, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of trimetallic compounds based on cobalt and nickel with ammonium fluoride-based complex for energy storage applications - Tsai-Mu Cheng; Pei-Chen Kuo; Yi-Chun Lai; Pin-Yan Lee; Chutima Kongvarhodom; Muhammad Saukani; Sibidou Yougbaré; Hung-Ming Chen; Kuo-Chuan Ho; Lu-Yin Lin (Journal of Environmental Chemical Engineering, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Pollution risk assessment and source apportionment of potentially toxic elements in agricultural soils using the APCS-MLR model: a case study near a non-ferrous metal smelting slag site in Gejiu, Yunnan - Chao-liang Peng; Zhe Wang; Ying Luo; Jia-Qian Zhang; Zhen-Long Zhang; Yi-ming Chen; Kai Ye; Wen-xue Lin; Jing-yan Zhang; Teng-jiao Xie (Environmental Monitoring and Assessment, 2025)

The calcined Mg-Al hydrotalcite for copper adsorption and passivation of copper-contaminated soil - Chun-Yan Cao; Ming-Hui Nie; Si-Lin Chen; Wen-Ling Long; Min Wang; Shuang Zhao; Xin Wan; Zhi-Guo Song (Process Safety and Environmental Protection, 2025)

Reinforcement learning-based backstepping sliding mode heading control for unmanned sailboats - Chen-Ming Li; Bao-Lin Zhang; Yan-Long Cao; Bo Yin (Ocean Engineering, 2025)

Beneficial impact of MTGase-modified fish gelatin on collagen supplementation in rats: Insights from serum metabolomics and gut microbiota - Chun-Yan Peng; Ting Fang; Hao-Bin Lin; Ni Zhang; Zi-Zi Hu; Hai-tao Wang; Ming-Hui Su; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Comprehensive modification of cratonic lithospheric mantle beneath the central North China Craton: Insights from Li isotope systematics of olivine xenocrysts in Cenozoic basalts - Yao Xu; Hong-Fu Zhang; Yan-Jie Tang; A-Bing Lin; Juan Zhang; Ming-Jie Zhang (Chemical Geology, 2025)

Remediation of Pb-contaminated soils using thermally activated Mg-Al hydrotalcite - Chun-Yan Cao; Wen-Ling Long; Si-Lin Chen; Ming-Hui Nie; Min Wang; Shuang Zhao; Xin Wan (Journal of Soils and Sediments, 2025)

Recoil control of nonlinear drilling riser systems via integral sliding mode schemes - Bao-Lin Zhang; Shou-Xiang Yan; Xian-Ming Zhang; Yanlong Cao; Xiuquan Liu (Ocean Engineering, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

The impact and mechanisms of YL-IPA08, a potent ligand for the translocator protein (18 kDa) on protection against LPS-induced depression and cognitive dysfunction in rodents - Lin-yu Cui; Jing-yao Duan; Jiao-zhao Yan; Jing-ya Wang; Peng Ren; Li-ming Zhang; Wen-zhi Guo; Wei Dai; Yun-feng Li (Metabolic Brain Disease, 2025)

Cumulus cells and the TNF-alpha signaling facilitate aging of ovine oocytes - Shuai Gong; Yan Zhang; Chao-Qun Cong; Guo-Liang Wang; Lin Jiang; Hong-Jie Yuan; Jing-He Tan; Ming-Jiu Luo (Theriogenology, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Acidosis induces autophagic cell death through ASIC1-mediated Akt/mTOR signaling in HT22 neurons - Miao Guo; Ming-Yue Qiu; Lin Zeng; Ya-Xiong Nie; Ya-Ling Tang; Yan Luo; Hong-Feng Gu (Toxicology, 2025)

Ultrathin LDH-coated SnO2 catalysts linked by hydrogen bonding for PMS activation via interlayer high-speed electron transfer channels: Performance and mechanism - Guangjie Lv; Haoyang Ye; Cui Lai; Dengsheng Ma; Xuerong Zhou; Xiuqin Huo; Hao Deng; Lin Tang; Tao Tong; Ming Yan; Shuyuan Hu; Lei Qin (Journal of Environmental Chemical Engineering, 2025)

Fire dynamics, fire generated pollutants, and acute health implications: A scaling law analysis of heavy-fuel-oil pool fires - Kuang-Chung Tsai; Li-Hsin Cheng; Chi-Fu Yeh; Tzu-Yan Tseng; Tzu-Ping Tseng; Li-Jen Huang; Shu-Hsing Yeh; Hui-Tsung Hsu; Ching-Ho Lin; Chin-Hsing Lai; Peter Brimblecombe; Ming-Jen Chen (Fuel, 2025)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenol from Chenopodium quinoa Willd.: Optimization and lipid-lowering activity - Xiao-tong Lin; Si-xuan Zhou; Zhi-peng Sun; Ming-yuan Cao; Tao Zhou; Li-yan Zhao; Gui-tang Chen (Food Chemistry, 2025)

Evidence of lower age, fast growth, and shrinking habitat in critically endangered croaker fish Larimichthys crocea - Chien-Hsiang Lin; Tai-Yan Lin; Aafaq Nazir; Yen-Chun Wang; Pei-Ling Wang; Yoshiyuki Iizuka; Kuang-Ti Li; Ming-Tsung Chung; Jen-Chieh Shiao (Estuarine, Coastal and Shelf Science, 2025)

Role of MFN2 in bovine embryonic development and the mitigation of ER stress - Shu-Ming Shi; Bing Hu; Zhi-Chao Chi; Lin-Yi Qu; Li-Ying Liu; Yu-Yan He; Guan-Lin Jia; Jing-Hang Li; Ilkeun Kong; Yong-Xun Jin; Xian-Feng Yu (Animal Reproduction Science, 2025)

Optimizing feeding frequencies in fish: A meta-analysis and machine learning approach - Ming Huang; Yan-Gen Zhou; Xiao-Gang Yang; Qin-Feng Gao; Ya-Na Chen; Yi-Chao Ren; Shuang-Lin Dong (Aquaculture, 2025)

PPARβ/δ agonist GW0742 mitigates acute liver damage induced by acetaminophen overdose in mice - Lin Wang; Jing-Hui Chen; Yan-Jing Zhang; Ming-Bao Zhang; Tao Zeng (Toxicology and Applied Pharmacology, 2025)

Data-driven optimization of nose profiles for water entry impact load reduction - Kai Lv; Enfan Lin; Yongze Liu; Zongbao Chen; Yexian Wang; Ming He; Jiale Yan; Pengyu Lv; Yantao Yang; Hongyuan Li; Huiling Duan (Ocean Engineering, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

A ZnO-nanorod/PEDOT:PSS nanocomposite functionalized bridge-like membrane type nanomechanical sensing device for ultrasensitive blood lead detection - Yi-Kuang Yen; Chia-Ming Yang; Chen-Ting Kao; Tzung-Hai Yen; Ragurethinam Shanmugam; Yan-Lin Chen; Hwai-En Lin (Analytica Chimica Acta, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Force mechanism analysis of composite microbial dust suppressants based on extracellular polymeric substances (EPS) mode components - Mei-Xuan Ha; Yu Liu; Yue Feng; Xiang-Ming Hu; Yan-Yun Zhao; Jin-Di Liu; Li Chen; Yan-Lin Qu (Journal of Environmental Management, 2024)

Planting halophytes increases the rhizosphere ecosystem multifunctionality via reducing soil salinity - Jin-Peng Hu; Yuan-Yuan He; Jian-Hong Li; Zhao-Long Lü; Yue-Wei Zhang; Yuan-Hong Li; Jia-Lü Li; Ming-Xu Zhang; Yan-Hua Cao; Jin-Lin Zhang (Environmental Research, 2024)

Gel electrolyte design for nonflammable lithium-ion batteries with high-rate and high-voltage characteristics - Po-Wei Huang; Qin-Cheng Zhang; Ming-Yuan Hung; Yan-Cheng Lin; Hong-Kang Tian; Yuh-Lang Lee; Jeng-Shiung Jan; Hsisheng Teng (Chemical Engineering Journal, 2024)

Fabrication of flexible Co3Fe7@Ti3C2Tx/TiO2/C@Spacer fabrics for tunable radar-infrared compatible stealth Inspired by layered structure of rock - Jiatong Yan; Chuanxi Lin; Shan Jiang; Weijie Wang; Ming Zhong; Hong Tang; Ronghui Guo (Chemical Engineering Journal, 2024)

Abundant small microplastics hidden in water columns of the Yellow Sea and East China Sea: Distribution, transportation and potential risk - Jia Lin; Jia-Yuan Zheng; Zhi-Geng Zhan; Yuan-Ming Zhao; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

High-altitude exposure leads to increased modularity of brain functional network with the increased occupation of attention resources in early processing of visual working memory - Jing Zhou; Nian-Nian Wang; Xiao-Yan Huang; Rui Su; Hao Li; Hai-Lin Ma; Ming Liu; De-Long Zhang (Cognitive Neurodynamics, 2024)

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

OsCOPT7 is involved in copper accumulation and transport through xylem - Mei Yan Guan; Zhenzhen Cao; Yu Chun Xia; Ping Xv; Xiao Yan Lin; Ming Xue Chen (Journal of Hazardous Materials, 2024)

Mining flotation reagents: Quantitative and robust analysis of metal-xanthate complexes in water - Wen-Jun Wu; Qing-Jun Zheng; Jing-Wen Liang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Nai-Xian Feng; Quan-Ying Cai; Lei Xiang; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Discovery and Exploration of Lipid-Modifying Drug Targets for ALS by Mendelian Randomization - Zheng Jiang; Xiao-Jing Gu; Wei-Ming Su; Qing-Qing Duan; Kang-Fu Yin; Yan-Lin Ren; Yi Wang; Bei Cao; Yong-Ping Chen (Molecular Neurobiology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

A hybrid algorithm based on the proposed square strategy and NSGA-II for ship pipe route design - Wei-qiang Yan; Ming-jun Yang; Yan Lin (Ocean Engineering, 2024)

The role of Pleistocene dispersal in shaping species richness of sky island wintergreens from the Himalaya-Hengduan Mountains - Xiao-Juan Cheng; Peter W. Fritsch; Yan-Jun Lin; Guo-Hong Li; Yan-Quan Chen; Ming-Ying Zhang; Lu Lu (Molecular Phylogenetics and Evolution, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Correction: Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Environmental evaluation of emerging bakery waste oil-derived sophorolipids production by performing a dynamic life cycle assessment - Yahui Miao; Xiaomeng Hu; Ming Ho To; Huaimin Wang; Zihao Qin; Jinhua Mou; Wei Yan; Guneet Kaur; Sophie L.K.W. Roelants; Carol Sze Ki Lin; Shauhrat S. Chopra (Sustainable Production and Consumption, 2024)

Anti-pancreatic cancer activity of cassane diterpenoids isolated from the seeds of Caesalpinia sappan mediated by autophagy activation via ROS/AMPK/mTORC1 pathway - Jia Su; De-Sheng Wang; Guo-Xian Hu; Yu-Yao Liu; Ming Hu; Ya Chen; Qi-Qi Wang; Run-Cheng Yan; Yun Wu; Yong-Jiao Li; Ke Ma; Yan-Yan Qi; et al. (Phytochemistry, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Congener-specific fate and impact of microcystins in the soil-earthworm system - Bai-Lin Liu; Peng-Fei Yu; Jing-Jie Guo; Li-Si Xie; Xiang Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Nai-Xian Feng; Quan-Ying Cai; Ce-Hui Mo; Qing X. Li (Journal of Hazardous Materials, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

3D Visualization of Whole Brain Vessels and Quantification of Vascular Pathology in a Chronic Hypoperfusion Model Causing White Matter Damage - Yang Wu; Jia Ke; Song Ye; Li-Li Shan; Shuai Xu; Shu-Fen Guo; Meng-Ting Li; Tian-Ci Qiao; Zheng-Yu Peng; Yi-Lin Wang; Ming-Yuan Liu; He Wang; et al. (Translational Stroke Research, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Extended state-based finite-time fuzzy optimal recoil control for nonlinear drilling riser systems after emergency disconnection - Bao-Lin Zhang; Ying-Tai Guo; Qing-Long Han; Yan Ji; Yanbin Wang; Xian-Ming Zhang; Zhihui Cai (Ocean Engineering, 2024)

Discrete recoil control system modelling and optimal recoil damping of deepwater drilling riser systems - Bao-Lin Zhang; Yue-Ting Sun; Yan-Dong Zhao; Qing-Long Han; Xian-Ming Zhang; Zhihui Cai (Ocean Engineering, 2024)

Microplastics in remote coral reef environments of the Xisha Islands in the South China Sea: Source, accumulation and potential risk - Jia Lin; Yuan-Ming Zhao; Zhi-Geng Zhan; Jia-Yuan Zheng; Qian-Zhi Zhou; Juan Peng; Yan Li; Xi Xiao; Jiang-Hai Wang (Journal of Hazardous Materials, 2024)

Arsenic effectively improves the degradation of fluorene by Rhodococcus sp. 2021 under the combined pollution of arsenic and fluorene - Hong-Peng Shi; Ying-Hao Zhao; Mei-Lin Zheng; Cheng-Yan Gong; Lei Yan; Ying Liu; Yong-Ming Luo; Zhi-Pei Liu (Chemosphere, 2024)

Predicting environmental impacts of smallholder wheat production by coupling life cycle assessment and machine learning - Chunxiao Yu; Gang Xu; Ming Cai; Yuan Li; Lijia Wang; Yan Zhang; Huilong Lin (Science of The Total Environment, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Experimental evaluation and theoretical modeling of eco-friendly bamboo scrimber-UHPC members with enhanced shear connectors - Youzhu Lin; Chen Wang; Ming Sun; Jiachuan Yan (Journal of Cleaner Production, 2024)

Sinomenine protects against atherosclerosis in apolipoprotein E-knockout mice by inhibiting of inflammatory pathway - Zhao Gao; Chao Yang; Guangwei Zeng; Ming Lin; Wei Li; Mengna Sun; Yantao Zhang; Beibei Fan; Yogesh Kumar; Kun Yan (Inflammopharmacology, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

The salt-tolerance of perennial ryegrass is linked with root exudate profiles and microflora recruitment - Yan-Hua Cao; Xiong-Wei Zhao; Gang Nie; Zhi-Yong Wang; Xin Song; Ming-Xu Zhang; Jin-Peng Hu; Qi Zhao; Yiwei Jiang; Jin-Lin Zhang (Science of The Total Environment, 2024)

Identical metamorphic record in distinct petrochemical systems: Case study of microscopically interlayered garnet amphibolite and metapelite from the Danba dome, SW China - Zhen M.G. Li; Yi-Chao Chen; Fred Gaidies; Yan-Lin Zhao; Chun-Ming Wu (Lithos, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Analyzing the correlation between quinolone-resistant Escherichia coli resistance rates and climate factors: A comprehensive analysis across 31 Chinese provinces - Yi-Chang Zhao; Zhi-Hua Sun; Ming-Xuan Xiao; Jia-Kai Li; Huai-yuan Liu; Hua-Lin Cai; Wei Cao; Yu Feng; Bi-Kui Zhang; Miao Yan (Environmental Research, 2024)

Porous MOFs-based self-assembled membrane with specific rebinding nanocages for selective recognition and separation at molecular level - Jingjing Zhen; Faguang Ma; Rongxin Lin; Ming Yan; Yilin Wu (Desalination, 2024)

TALE-based organellar genome editing and gene expression in plants - Jer-Young Lin; Yu-Chang Liu; Yan-Hao Tseng; Ming-Tsair Chan; Ching-Chun Chang (Plant Cell Reports, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Taste traces: Capsaicin and sweeteners as anthropogenic markers in municipal wastewater - Xue-Ting Shao; Yan-Song Wang; Yue-Tong Zhao; Jian-Guo Lin; Wei Pei; Ming-Xing Guo; De-Gao Wang (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Undescribed matrine-type alkaloids from Sophora alopecuroides with anti-inflammatory activity - Ding Luo; Jia-Wen Zou; Jing-Hao Wang; He Tian; Hua-Yan Xie; Tian-Xi Zhu; Hui-Hui Zhu; Lu-Ming Deng; Chun-Lin Fan; Hao Wang; Guo-Cai Wang; Yu-Bo Zhang (Phytochemistry, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

MiR-7 deficiency promotes Th1 polarization of CD4+T cells and enhances the antitumor effect in adoptive cell therapy for lung cancer - Xian Chang; Juanjuan Zhao; Ya Zhou; Mengmeng Guo; Yaping Yan; Ya Wang; Xu Zhao; Jing Yang; Chao Chen; Lin Tang; Ming Qin; Lin Xu (Immunologic Research, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Enhanced humus synthesis from Chinese medicine residues composting by lignocellulose-degrading bacteria stimulation: Upregulation of key enzyme activity and neglected indirect effects on humus formation - Chuan-Ming Xing; Zi-Lin He; Tian Lan; Bo Yan; Qi Zhao; Qing-Lian Wu; Hua-Zhe Wang; Cai-Xia Wang; Wan-Qian Guo (Science of The Total Environment, 2024)

Melatonin alleviates Hg toxicity by modulating redox homeostasis and the urea cycle in moss - Wen-Yue Hu; Hao-Tian Mao; Xiao-Yan Yin; Jing-Yi Chen; An-Qi He; Lin-Yan Huang; Zhong-Wei Zhang; Shu Yuan; Ming Yuan; Yan-Qiu Su; Yang-Er Chen (Science of The Total Environment, 2024)

Quaternary stratigraphic architecture of the Pearl River Mouth continental shelf, northern South China Sea: Unraveling stratigraphic imprints of tectonism, paleoceanography, and climate change - Haiteng Zhuo; Xin Nie; Ming Su; Wei Zhou; Yaping Lei; Yingmin Wang; Xuechao Peng; Yan Qiu; Weiyao Yan; Li'e Lin (Sedimentary Geology, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

An acidic heteropolysaccharide rich in galactose and arabinose derived from ginger: Structure and dynamics - Xiao-tong Lin; Bo-xian Xiao; Jun-ping Liu; Ming-yuan Cao; Zhi-ping Yang; Li-yan Zhao; Gui-tang Chen (Food Bioscience, 2023)

Non-targeted analysis and risk assessment of intentionally and non-intentionally added substances migrating from the emerging biodegradable food contact material poly(butylene adipate-co-terephthalate)/modified starch blend film - Jun Lin; Wei-Liang Wu; Ai-Hua Zhong; Yan-Ping Xian; Huai-Ning Zhong; Ben Dong; Ming Liang; Jun-Peng Hu; Yong-Ning Wu; Xing-Fen Yang; Hai-Xia Sui; Quan Zhou (Food Packaging and Shelf Life, 2023)

Face-to-face conducting mechanism enabled by Si-C bonds for binder free Si@CNTs electrode - Zhi Yong Zhang; Zhe Fei Sun; Yan Liu; Bing Sheng Liu; Lin Shan Luo; Peng Fei Su; Chao Fei Lan; Shi Sheng Guo; Zi Qi Zhang; Xiang Han; Wei Huang; Zi Ping Wu; et al. (Chemical Engineering Journal, 2023)

The Daily Intake Levels of Copper, Selenium, and Zinc Are Associated with Osteoarthritis but Not with Rheumatoid Arthritis in a Cross-sectional Study - Wei-ming Yang; Jiao-feng Lv; Yuan-yuan Wang; Yan-mei Xu; Jin Lin; Jing Liu; Juan-juan Chen; Xiao-zhong Wang (Biological Trace Element Research, 2023)

Effects of different Solanum sect. Solanum (Solanaceae) straw amendments on selenium accumulation and growth of grapevine - Kewen Huang; Xu Chen; Ran Zhang; Yiping Dong; Qunxian Deng; Yan Huang; Lei Liu; Ting Wang; Ming’an Liao; Lijin Lin (Acta Physiologiae Plantarum, 2023)

Enhancing acidification efficiency of vegetable wastes through heat shock pretreatment and initial pH regulation - Fanfan Cai; Ming Lin; Ligong Wang; Chao Song; Yan Jin; Guangqing Liu; Chang Chen (Environmental Science and Pollution Research, 2023)

Traditional Chinese medicine bufalin inhibits infectious pancreatic necrosis virus genogroups I and V infection in vitro and in vivo - Jing-Zhuang Zhao; Lin-Fang Li; Li-Ming Xu; Yi-Zhi Shao; Guang-Ming Ren; Qi Liu; Tong-Yan Lu (Aquaculture, 2023)

Permafrost change and its engineering effects under climate change and airport construction scenarios in northeast China - Ming Guo; Yan Lu; Wenbing Yu; Lilin Xu; Da Hu; Lin Chen (Transportation Geotechnics, 2023)

A simultaneous facility location and vehicle routing problem with recyclable express packaging consideration for sustainable city logistics - Yuhe Shi; Yun Lin; Songyi Wang; Haolin Wen; Ming K. Lim; Yan Li (Sustainable Cities and Society, 2023)

Sensory-directed isolation and identification of an intense salicin-like bitter compound in infected teas with bird’s eye spot disease - Jingna Yan; Yiwen Miao; Jingyun Zhou; Rui Huang; Hongwei Dai; Ming Liu; Yunzhi Lin; Yingjuan Chen; Chi-Tang Ho; Huarong Tong; Qing Meng (Food Research International, 2023)

3D printing of customizable and lightweight multilayer MXene/nanocellulose architectures for tunable electromagnetic interference shielding via direct ink writing - Lei Chen; Tian Mai; Xing-Xiang Ji; Pei-Lin Wang; Meng-Yu Qi; Qi Liu; Yan Ding; Ming-Guo Ma (Chemical Engineering Journal, 2023)

Stretchable textile with ultra-high electromagnetic interference shielding performance based on porous wrinkled conductive network - Tai-Bao Yang; Ji-You Zong; Hao Lin; Ding-Xiang Yan; Jun Lei; Zhong-Ming Li (Chemical Engineering Journal, 2023)

Effect of the inoculation of Phanerochaete chrysosporium on nitrogen migration and organic matter conversion during electrolytic manganese residue composting - Xiangyu Peng; Ming Yan; Qingqing Xie; Lan Gao; Xiaojuan Pu; Yukui Fu; Hanwen Liu; Min Cheng; Piao Xu; Danlian Huang; Lin Tang (Bioresource Technology, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Anodic oxidation-accelerated self-reconstruction of tri-metallic Prussian blue analogue toward robust oxygen evolution reaction performance - Thi Xuyen Nguyen; Kai-Hsiang Yang; Yan-Jia Huang; Yen-Hsun Su; Oliver Clemens; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

Insight into the selective oxidation behavior of organic pollutants via Ni-N4-C mediated electron transfer pathway - Huchuan Yan; Cui Lai; Shiyu Liu; Dongbo Wang; Xuerong Zhou; Mingming Zhang; Ling Li; Dengsheng Ma; Fuhang Xu; Xiuqin Huo; Lin Tang; Ming Yan; et al. (Chemical Engineering Journal, 2023)

ROS-mediated mitophagy and necroptosis regulate osteocytes death caused by TCP particles in MLO-Y4 cells - Pei Yang; Bingbing Xu; Ruirong Zhu; Tao Zhang; Zihan Wang; Qiao Lin; Ming Yan; Zhangsen Yu; Hongjiao Mao; Yun Zhang (Toxicology, 2023)

Early Paleozoic subduction imprints of the Proto-Tethys Ocean: Evidence from the Appinite–Diorite–Granodiorite complex in East Kunlun, Northern Tibet - Yang-Ming Hu; Xiao-Wei Li; Xuan-Xue Mo; Lin Li; Kai Wang; Bing-Zhang Wang; Xiao-Ping Gong; Guo-Chen Dong; Yan-Bin Liu (Lithos, 2023)

Phosphorylation modification orchestrates the functionalities of peroxin 14 in filamentous entomopathogenic fungus Beauveria bassiana - Hai-Yan Lin; Ming-Guang Feng; Sheng-Hua Ying (Fungal Biology, 2023)

Toward ultra-high efficiency tandem OLEDs: Benzothiazole-based bipolar hosts and specific device architectures - Jui-Ming Wang; Ting-Chun Lee; Chia-Chen Chung; Wun-Yu Chen; Sih-Yu Wu; Yan-Ding Lin; Yuan Jay Chang; Chin-Wei Lu; Chih-Hao Chang (Chemical Engineering Journal, 2023)

Bidirectional crosstalk of the cAMP/ROS-dependent signaling pathways in inflammatory macrophage: An activation of formononetin - Lan-Fang Zhang; Xiao-Yan Zhang; Ai-Cheng Wang; Yi-Jia Feng; Xiao-Ming Qi; Yuan-Lin Zhang; Qing-Fang Li; Yuan-Biao Qiao; Qing-Shan Li (Toxicology and Applied Pharmacology, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Population structure and genetic diversity of Triticum araraticum Jakubz. and Triticum timopheevii Zhuk. - Ting Peng; Xiaomei Jiang; Dinghao Wang; Minghu Zhang; Xin Liu; Ming Hao; Wei Li; Dengcai Liu; Bo Jiang; Lin Huang; Shunzong Ning; Zhongwei Yuan; et al. (Genetic Resources and Crop Evolution, 2023)

Inhibition of CDK9 exhibits anticancer activity in hepatocellular carcinoma cells via targeting ribonucleotide reductase - Jiunn-Chang Lin; Tsang-Pai Liu; Yan-Bin Chen; Tun-Sung Huang; Tung-Ying Chen; Pei-Ming Yang (Toxicology and Applied Pharmacology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Purification and identification of xanthine oxidase inhibitory peptides from enzymatic hydrolysate of α-lactalbumin and bovine colostrum casein - Yi-Fang Gao; Meng-Qi Liu; Zhong-Han Li; Han-Lin Zhang; Jia-Qi Hao; Bo-Hao Liu; Xiao-Yan Li; Yu-Qi Yin; Xiao-Hui Wang; Qian Zhou; Di Xu; Bao-Ming Shi; et al. (Food Research International, 2023)

MOF-initiated imprinted self-supporting basswood membranes for precise recognition and separation of artemisinin - Shuhan Jia; Faguang Ma; Rongxin Lin; Ming Yan; Yilin Wu (Journal of Environmental Chemical Engineering, 2023)

High entropy promoted active site in layered double hydroxide for ultra-stable oxygen evolution reaction electrocatalyst - Thi Xuyen Nguyen; Chia-Chien Tsai; Van Thanh Nguyen; Yan-Jia Huang; Yen-Hsun Su; Siang-Yun Li; Rui-Kun Xie; Yu-Jung Lin; Jyh-Fu Lee; Jyh-Ming Ting (Chemical Engineering Journal, 2023)

A new chamigrane sesquiterpene from the rice fermentation of Antrodiella albocinnamomea - Min Guo; Ying-Zhong Liang; Xiu-Ming Cui; Lin-Jiao Shao; Yin-Fei Li; Xiao-Yan Yang (Natural Product Research, 2023)

Polyethylene and polypropylene microplastics reduce chemisorption of cadmium in paddy soil and increase its bioaccessibility and bioavailability - Jing-Jie Guo; Fen Li; Hai-Chuan Xiao; Bai-Lin Liu; Lin-Nan Feng; Peng-Fei Yu; Can Meng; Hai-Ming Zhao; Nai-Xian Feng; Yan-Wen Li; Quan-Ying Cai; Lei Xiang; et al. (Journal of Hazardous Materials, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

Bona fide upcycling strategy of anhydride cured epoxy and reutilization of decomposed dual monomers into multipurpose applications - Lin Shao; Yu-Chung Chang; Baoming Zhao; Xinyan Yan; Brian J. Bliss; Ming-en Fei; Chenhao Yu; Jinwen Zhang (Chemical Engineering Journal, 2023)

Bilayer metal-organic frameworks/MXene/nanocellulose paper with electromagnetic double loss for absorption-dominated electromagnetic interference shielding - Tian Mai; Wen-Yan Guo; Pei-Lin Wang; Lei Chen; Meng-Yu Qi; Qi Liu; Yan Ding; Ming-Guo Ma (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

Variable p53/Nrf2 crosstalk contributes to triptolide-induced hepatotoxic process - Zhenyan Hou; Miao Yan; Huixiang Li; Weida Wang; Shen You; Mingjin Wang; Tingting Du; Hui Gong; Wenqun Li; Lin Guo; Shanshan Wei; Bikui Zhang; et al. (Toxicology Letters, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Diverse alkaloids from the aerial parts of Aconitum carmichaelii and antiproliferative activity of costemline via inhibiting SIRT1/ROCK1/P-STAT3 pathways - Yin-Lin Zhou; Duan-Na Zhang; Ji-Xu Qiao; Jing Wu; Yong-Ming Yan; Zhi-Xing Cao; Cheng Peng; Yu-Zhu Tan (Phytochemistry, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Source-specific health risk analysis on atmospheric hazardous volatile organic compounds (HVOCs) in Nanjing, East China - Yu-Chi Lin; Zi-Jin Zhang; Meng-Yao Cao; Mei-Yi Fan; Ahsan Mozaffar; Ming-Yuan Yu; Feng Xie; Yan-Lin Zhang (Atmospheric Environment, 2023)

Revealing microcystin-LR ecotoxicity to earthworm (Eisenia fetida) at the intestinal cell level - Xiang Liu; Jin-Cheng Ye; Fen Li; Rong-Jun Gao; Xiao-Xiao Wang; Ji-Liang Cheng; Bai-Lin Liu; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Hai-Ming Zhao; Ce-Hui Mo; et al. (Chemosphere, 2023)

Observer-based dynamic optimal recoil controller design for deepwater drilling riser systems - Wei Zhang; Bao-Lin Zhang; Qing-Long Han; Yue-Ting Sun; Yan Ji; Dawei Zhang; Xian-Ming Zhang (Ocean Engineering, 2023)

Functional characterization of two homologs of yeast acetyl-coenzyme A synthetase in the entomopathogenic fungus Beauveria bassiana - Jia-Hui Lei; Hai-Yan Lin; Jin-Li Ding; Ming-Guang Feng; Sheng-Hua Ying (Archives of Microbiology, 2022)

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Nematicidal activity of volatile organic compounds produced by Bacillus altitudinis AMCC 1040 against Meloidogyne incognita - Lin Ye; Jian-Yu Wang; Xiao-Fang Liu; Qi Guan; Nong-Xiao Dou; Jian Li; Qian Zhang; Yan-Ming Gao; Min Wang; Jian-She Li; Bo Zhou (Archives of Microbiology, 2022)

Systematic contributions of CFEM domain‐containing proteins to iron acquisition are essential for interspecies interaction of the filamentous pathogenic fungus Beauveria bassiana - Yue‐Jin Peng; Jia Hou; Hao Zhang; Jia‐Hui Lei; Hai‐Yan Lin; Jin‐Li Ding; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2022)
Summary Common in fungal extracellular membrane (CFEM) domain is unique in fungal proteins and some of which contribute to iron acquisition in yeast. However, their roles in iron acquisition remain largely unknown in filamentous fungi. In this study, 12 CFEM‐containing proteins were bioinformatically identified in the filamentous entomopathogenic fungus Beauveria bassiana , and the roles of 11 genes were genetically characterized. Transmembrane helices were critical for their association with intracellular membranes, and their number varied among proteins. Eleven CFEM genes significantly contribute to vegetative growth under iron starvation and virulence. Notably, the virulence of most disruptants could be significantly weakened by a decrease in iron availability, in which the virulence of Δ Bbcfem7 and 8 strains was partially recovered by exogenous hemin. Δ Bbcfem7 and 8 mutants displayed defective competitiveness against the sister entomopathogenic fungus Beauveria brongniartii . All 11 disruptants displayed impaired growth in the antagonistic assay with the saprotrophic fungus Aspergillus niger , which could be repressed by exogenous ferric ions. These findings not only reveal the systematic contributions of CFEM proteins to acquire two forms of iron (i.e. heme and ferric ion) in the entire lifecycle of entomopathogenic fungi but also help to better understand the mechanisms of fungus–host and inter–fungus interactions.

Testing the transfer functions for the Geonor T-200B and Chinese standard precipitation gauge in the central Qinghai—Tibet Plateau - Le-le Zhang; Li-ming Gao; Ji Chen; Lin Zhao; Ke-long Chen; Jing-yi Zhao; Guo-jun Liu; Ting-xi Song; Yan-kun Li (Journal of Mountain Science, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

First report of Euphorbia leaf curl virus infecting Passiflora edulis in Fujian province, China - Ting Ye; Guo-Hua Zheng; Ying Guo; Yan-Lin Ming (Journal of Plant Pathology, 2022)

Bioactive compounds derived from the marine-derived fungus MCCC3A00951 and their influenza neuraminidase inhibition activity in vitro and in silico - Shun-Zhi Liu; Feng-Ming He; Yan-lin Bin; Chu-Fang Li; Bao-Ying Xie; Xi-Xiang Tang; Ying-Kun Qiu (Natural Product Research, 2021)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Timing and magnitude of climatic extremes differentially elevate mortality but enhance recovery in a fish population - Ming‐Chih Chiu; Shih‐Hsun Chang; Yu‐Ting Yen; Lin‐Yan Liao; Hsing‐Juh Lin (Global Change Biology, 2021)
The countervailing effects of disturbances (e.g., high mortality and enhanced recovery) on population dynamics can occur through demographic processes under rapidly increasing climatic extremes. Across an extreme‐event gradient, we mechanistically demonstrated how dramatic changes in streamflow have affected the population persistence of endangered salmon in monsoonal Taiwan over a three‐decade period. Our modeling indicated that the dynamics of the age‐structured population were attributed to demographic processes, in which extensive mortality was characterized as a function of climatic extremes and vulnerability in the young stage of fish. In the stochastic simulations, we found that the extensive mortality and high proportion of large fish resulted from extreme flooding, which caused high values of postimpact population recovery. Our empirical evidence suggests that the magnitudes and timing of disturbance can explain the population persistence when facing climatic extremes and thereby challenges the understanding of the mechanistic drivers of these countervailing phenomena under changing environmental conditions.

Pseudomonas nanhaiensis sp. nov., a lipase-producing bacterium isolated from deep-sea sediment of the South China Sea - Yu Pang; Yage Zhang; Mengru Chen; Wei Lu; Ming Chen; Yongliang Yan; Min Lin; Wei Zhang; Zhengfu Zhou (Antonie van Leeuwenhoek, 2021)

Two new cephalochromin derivative from the Alternaria sp. ZG22 - Xin-Ming Song; Xue-Ming Zhou; Ya-Ling Li; Li-Bing Huang; Cai-Cui Chen; Yan Gao; Lin He; Xiao-qun Mao; Bing Chen; Jing-Wen Liu; Hui-Jie Liu; Xiao-Ping Song; et al. (Natural Product Research, 2021)

Shared and specific patterns of structural and functional thalamo-frontal disturbances in manic and euthymic pediatric bipolar disorder - Yi-Bing Guo; Wei-Jia Gao; Zhi-Liang Long; Wei-Fang Cao; Dong Cui; Yong-Xin Guo; Qing Jiao; Jian-Feng Qiu; Lin-Yan Su; Guang-Ming Lu (Brain Imaging and Behavior, 2021)
Bipolar disorder (BD) is clinically defined by alternating depressive and manic episodes with a separated period of euthymia. Thalamo-frontal loop plays vital role in psychotic symptoms, altered motor control and executive difficulties in BD. It remains unclear that structural and functional alterations of thalamo-frontal loop among the different mood states in BD, especially in pediatric BD(PBD). Twenty manic PBD (mPBD), 20 euthymic PBD (ePBD) and 19 healthy controls (HCs) were included in the study. By analyzing the T1 images and fMRI signals, thalamus volume and frontal grey matter cortical thickness were tested, and functional connectivity (FC) between bilateral thalamus and frontal cortex was calculated. Relationship between clinical indices and thalamo-frontal FC was also evaluated in mPBD and ePBD adolescents. Compared to HCs, the cortical thickness of left middle frontal gyrus (MFG), bilateral superior frontal gyrus (SFG) was significantly decreased in both mPBD and ePBD patients, and volume of left thalamus and cortical thickness of right MFG significantly decreased in mPBD patients. Compared to that of the HCs and ePBD subjects, thalamo-frontal hyperconnectivity with MFG was found in mPBD, and compared with that of HCs, thalamo-frontal hypoconnectivity with precentral gyrus/SFG was found in ePBD. In ePBD patients, episode times positively correlated with FC values between thalamus and precentral gyrus. The findings of the present study demonstrate detailed knowledge regarding shared and specific structural and functional disruption in thalamo-frontal loop in mPBD and ePBD subjects. Thalamo-frontal abnormalities reported in adult BD subjects were also observed in adolescent BD patients, and thalamo-frontal dysfunction may be a crucial treatment target in BD.

Comparison of pramipexole and levodopa/benserazide combination therapy versus levodopa/benserazide monotherapy in the treatment of Parkinson’s disease: a systematic review and meta-analysis - De-Qi Jiang; Qing-Min Zang; Li-Lin Jiang; Yan Wang; Ming-Xing Li; Jing-Yi Qiao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Effects of mutual grafting Solanum photeinocarpum from two ecosystems on physiology and selenium absorption of their offspring under selenium stress - Kewen Huang; Yan Wang; Xiaohan Wei; Yuhui Bie; Huixuan Zhou; Lili Deng; Lijin Lin; Ming’an Liao (Acta Physiologiae Plantarum, 2021)

Icaritin Inhibits Skin Fibrosis through Regulating AMPK and Wnt/β-catenin Signaling - Ming Li; Qingmei Liu; Shan He; Xiangzhen Kong; Jinpei Lin; Yan Huang; Wenyu Wu; Jinfeng Wu (Cell Biochemistry and Biophysics, 2021)

QTL mapping of the genetic basis of stem diameter in soybean - Chong-Yuan Sun; Yu-Ming Yang; Lin Jia; Xiao-Qian Liu; Huan-Qing Xu; Hai-Yan Lv; Zhong-Wen Huang; Dan Zhang (Planta, 2021)

Carbon isotope variations of modern soils in the eastern margin of the Tibetan Plateau and their controlling factors - Lin Qi; Yan-song Qiao; Zong-xiu Liu; Sha-sha Peng; Yu Cheng; Yan Wang; Xu-jiao Zhang; Ming-zhong Tian; Shuai-bin Yang; Wen-bin Bai (Journal of Mountain Science, 2021)

Identification of contaminants as members of the Bacillus pumilus group and analysis of contamination sources in the cultivation of Pleurotus geesteranus mushrooms - Na Lu; Wei-Dong Yuan; You-Liang Wu; Ji-Ling Song; Lin Ma; Wei-Ke Wang; Jing Yan; Zai-Ming Chen; Qing Chen (Journal of Plant Pathology, 2021)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Intrusion of Kuroshio Helps to Diminish Coastal Hypoxia in the Coast of Northern South China Sea - Hon-Kit Lui; Chen-Tung Arthur Chen; Wei-Ping Hou; Jian-Ming Liau; Wen-Chen Chou; You-Lin Wang; Chau-Ron Wu; Jay Lee; Yi-Chia Hsin; Yan-Yu Choi (Frontiers in Marine Science, 2020)

One new sterpurane sesquiterpene from cultures of the basidiomycete Pholiota nameko - Wan-Rong Niu; Cong-Liang Guo; Deng-Ji Lou; Rui-Ting Li; Qiao Xiang; Yu-Lin Zou; Xiu-Ming Cui; Xiao-Yan Yang (Natural Product Research, 2020)

Sodium Para-aminosalicylic Acid Reverses Changes of Glutamate Turnover in Manganese-Exposed Rats - Zhao-Cong Li; Fang Wang; Shao-Jun Li; Lin Zhao; Jun-Yan Li; Yue Deng; Xiao-Juan Zhu; Yu-Wen Zhang; Dong-Jie Peng; Yue-Ming Jiang (Biological Trace Element Research, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Two new xanthone glycosides from Swertia punicea Hemsl. and their anti-inflammatory activity - Lin-Yun Mou; Hai-Yan Wu; En-Guang Ma; Ming-Feng Wang; Yan-Qing Duan; Sheng Lei; Gan-Peng Li (Natural Product Research, 2020)

Opportunistic bacteria use quorum sensing to disturb coral symbiotic communities and mediate the occurrence of coral bleaching - Jin Zhou; Zi‐Jun Lin; Zhong‐Hua Cai; Yan‐Hua Zeng; Jian‐Ming Zhu; Xiao‐Peng Du (Environmental Microbiology, 2020)
Summary Coral associated microorganisms, especially some opportunistic pathogens can utilize quorum‐sensing (QS) signals to affect population structure and host health. However, direct evidence about the link between coral bleaching and dysbiotic microbiomes under QS regulation was lacking. Here, using 11 opportunistic bacteria and their QS products (AHLs, acyl‐homoserine‐lactones), we exposed Pocillopora damicornis to three different treatments: test groups (A and B: mixture of AHLs‐producing bacteria and cocktail of AHLs signals respectively); control groups (C and D: group A and B with furanone added respectively); and a blank control (group E: only seawater) for 21 days. The results showed that remarkable bleaching phenomenon was observed in groups A and B. The operational taxonomic units‐sequencing analysis shown that the bacterial network interactions and communities composition were significantly changed, becoming especially enhanced in the relative abundances of Vibrio , Edwardsiella , Enterobacter , Pseudomonas , and Aeromonas . Interestingly, the control groups (C and D) were found to have a limited influence upon host microbial composition and reduced bleaching susceptibility of P. damicornis . These results indicate bleaching's initiation and progression may be caused by opportunistic bacteria of resident microbes in a process under regulation by AHLs. These findings add a new dimension to our understanding of the complexity of bleaching mechanisms from a chemoecological perspective.

Involvement of the JNK signaling in granular corneal dystrophy by modulating TGF-β-induced TGFBI expression and corneal fibroblast apoptosis - Danyao Nie; Xinhua Liu; Yuan Wang; Wenling He; Ming Li; Yun Peng; Jing Zhang; Liangnan Sun; Zonghui Yan; Lin Ye (In Vitro Cellular & Developmental Biology - Animal, 2020)

(±)-Quassidine K, a pair of cytotoxic bis- β -carboline alkaloid enantiomers from Picrasma quassioides - Xin-Ming Guo; Fei Li; Fang-Fang Zheng; Na-Na Gong; Yan Li; Wen-Zhou Feng; Lin Tian (Natural Product Research, 2020)

Mbp1, a component of the MluI cell cycle box‐binding complex, contributes to morphological transition and virulence in the filamentous entomopathogenic fungus Beauveria bassiana - Jin‐Li Ding; Hai‐Yan Lin; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2020)
Summary The Mbp1 protein functions as a DNA‐binding protein in the MluI cell cycle box‐binding complex and plays significant roles in yeast development. In this study, an ortholog of yeast Mbp1, BbMbp1, was characterized in a filamentous insect mycopathogen, Beauveria bassiana . BbMbp1 plays an important role in morphological changes under aerial and liquid environments. On the aerial surface, BbMbp1 was indispensable for the biogenesis of conidiophores and conidiation. Under submerged conditions, the ∆ BbMbp1 mutant displayed abnormal spore‐producing structures, with a dramatic decrease in blastospore yield (~95%). The virulence of the ∆ BbMbp1 mutant was notably weakened, which might be due to the defect in in vivo blastospore formation in the insect. Moreover, disruption of BbMbp1 resulted in a substantial reduction in hyphal growth on cadavers. Comparative transcriptomics revealed that BbMbp1 mediated different transcriptomes during the formation processes of conidia and blastospores. Yeast one‐hybrid assays demonstrated that BbMbp1 was required for transcriptional control of a cell wall protein gene, BbCwp , and an integral membrane protein gene, BbImp that played significant roles in conidiation and blastospore formation respectively. Our results demonstrate that BbMbp1 contributes to the morphological transitions in the pathogenic and saprophytic growth of B . bassiana via different genetic pathways.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The High-Frequency Decay Parameter (Kappa) in Taiwan - Shun-Chiang Chang; Kuo-Liang Wen; Ming-Wey Huang; Chun-Hsiang Kuo; Che-Min Lin; Chun-Te Chen; Jyun-Yan Huang (Pure and Applied Geophysics, 2019)

A new indole-type alkaloid from the roots of Clematis florida var. plena - Kai-Hui Sun; Xin-Hua Ma; Xian-Ming Zeng; Zhong-Yue Lin; Yu-Mei Cai; Hai-Tao Zhang; Xiao-Yan Lin; Shi-Biao Feng; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2019)

Comparative Analysis of SUS Gene Family between Saccharum officinarum and Saccharum spontaneum - Yan Shi; Huimin Xu; Qiaochu Shen; Jingxian Lin; Yongjun Wang; Xiuting Hua; Wei Yao; Qingyi Yu; Ray Ming; Jisen Zhang (Tropical Plant Biology, 2019)

A breeding strategy targeting the secondary gene pool of bread wheat: introgression from a synthetic hexaploid wheat - Ming Hao; Lianquan Zhang; Laibin Zhao; Shoufen Dai; Aili Li; Wuyun Yang; Die Xie; Qingcheng Li; Shunzong Ning; Zehong Yan; Bihua Wu; Xiujin Lan; et al. (Theoretical and Applied Genetics, 2019)

First report of lettuce big-vein associated varicosavirus infecting lettuce in China - Guo-Hua Zheng; Ting Ye; Fu-Rong Liao; Wen-Zhu Zhang; Yan-Lin Ming (Journal of Plant Pathology, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Interhemispheric functional connectivity for Alzheimer’s disease and amnestic mild cognitive impairment based on the triple network model - Zheng-luan Liao; Yun-fei Tan; Ya-ju Qiu; Jun-peng Zhu; Yan Chen; Si-si Lin; Ming-hao Wu; Yan-ping Mao; Jiao-jiao Hu; Zhong-xiang Ding; En-yan Yu (Journal of Zhejiang University-SCIENCE B, 2018)

Late Cretaceous basalts and rhyolites from Shimaoshan Group in eastern Fujian Province, SE China: age, petrogenesis, and tectonic implications - Xi-Yao Li; San-Zhong Li; Yan-Hui Suo; Li-Ming Dai; Ling-Li Guo; Feng-Jian Ge; Pei-Jun Lin (International Geology Review, 2018)

Elatostema brachyodontum subsp. lengshuiheensis (Urticaceae), a new subspecies from Guizhou, China - Yun Lin; Ming-Tai An; Zhi-Rong Yang; Yan-Qiang Dai; Deng-Li Yu (Kew Bulletin, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Gender-Related Hippocampal Proteomics Study from Young Rats After Chronic Unpredicted Mild Stress Exposure - Lin-Na Ning; Teng Zhang; Jiang Chu; Na Qu; Li Lin; Ying-Yan Fang; Yan Shi; Peng Zeng; Er-Li Cai; Xiao-Ming Wang; Qun Wang; You-Ming Lu; et al. (Molecular Neurobiology, 2018)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

Epigenetic silencing of PRSS3 provides growth and metastasis advantage for human hepatocellular carcinoma - Bonan Lin; Xiaomeng Zhou; Shuye Lin; Xiaoyue Wang; Meiying Zhang; Baoping Cao; Yan Dong; Shuai Yang; Ji Ming Wang; Mingzhou Guo; Jiaqiang Huang (Journal of Molecular Medicine, 2017)

Contaminant characteristics and environmental risk assessment of heavy metals in the paddy soils from lead (Pb)-zinc (Zn) mining areas in Guangdong Province, South China - Da-Mao Xu; Bo Yan; Tao Chen; Chang Lei; Han-Zhi Lin; Xian-Ming Xiao (Environmental Science and Pollution Research, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Two new flavans from the roots of Dianella ensifolia (L.) DC - Ben-Qin Tang; Shu-Sheng Huang; Ye-Er Liang; Jian-Bo Sun; Yan Ma; Bao Zeng; Simon Ming-Yuen Lee; Jian-Lin Lu (Natural Product Research, 2017)

Quantification of mycotoxins in vegetable oil by UPLC-MS/MS after magnetic solid-phase extraction - Yan Zhao; Li-Hong Wan; Xiao-Lin Bai; Yi-Ming Liu; Feng-Ping Zhang; Yao-Min Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

A study on the oil-based drilling cutting pyrolysis residue resource utilization by the exploration and development of shale gas - Chao-qiang Wang; Ji-zhong Jin; Xiao-yan Lin; De-ming Xiong; Xu-dong Mei (Environmental Science and Pollution Research, 2017)

Decreased interaction between ZO-1 and occludin is involved in alteration of tight junctions in transplanted epiphora submandibular glands - Chong Ding; Xin Cong; Xue-Ming Zhang; Sheng-Lin Li; Li-Ling Wu; Guang-Yan Yu (Journal of Molecular Histology, 2017)

A new diphenyl ether derivative from Mirabilis himalaica - Si-Yu Zhou; Guo-Wei Wang; Yan-Lin Zou; Li-Qing Deng; Ming-Xu Liu; Zhi-Hua Liao; Xiao-Zhong Lan; Min Chen (Natural Product Research, 2017)

Integrative multi-omics analysis revealed SNP-lncRNA-mRNA (SLM) networks in human peripheral blood mononuclear cells - Wei Xia; Xiao-Wei Zhu; Xin-Bo Mo; Long-Fei Wu; Jian Wu; Yu-Fan Guo; Ke-Qin Zeng; Ming-Jun Wang; Xiang Lin; Ying-Hua Qiu; Lan Wang; Pei He; et al. (Human Genetics, 2017)

Efficient synthesis of (S)-N-Boc-3-hydroxypiperidine using an (R)-specific carbonyl reductase from Candida parapsilosis - Jingjing Chen; Ming Yan; Lin Xu (World Journal of Microbiology and Biotechnology, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

Rapid determination of gizzerosine in fish meals using microchip capillary electrophoresis with laser-induced fluorescence detection - Meng-Wei Xiao; Xiao-Lin Bai; Pei-Li Xu; Yan Zhao; Li Yang; Yi-Ming Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

A mechanism of low molecular weight fucoidans degraded by enzymatic and acidic hydrolysis for the prevention of UVB damage - Pai-An Hwang; Ming-De Yan; Ko-Liang Kuo; Nam Nhut Phan; Yen-Chang Lin (Journal of Applied Phycology, 2017)

Chemical composition and antioxidant activities of essential oils from different parts of the oregano - Fei Han; Guang-qiang Ma; Ming Yang; Li Yan; Wei Xiong; Ji-cheng Shu; Zhi-dong Zhao; Han-lin Xu (Journal of Zhejiang University-SCIENCE B, 2017)

Incentive effect of bentonite and concrete admixtures on stabilization/solidification for heavy metal-polluted sediments of Xiangjiang River - Ming Yan; Guangming Zeng; Xiaoming Li; Jianmin He; Guiqiu Chen; Danlian Huang; Lin Tang; Cui Lai; Chang Zhang; Xiaodong Li; Lichao Wang; Zhi Guo; et al. (Environmental Science and Pollution Research, 2017)

In Situ Field-Scale Remediation of Low Cd-Contaminated Paddy Soil Using Soil Amendments - Lin-feng Li; Shao-ying Ai; Yan-hong Wang; Ming-deng Tang; Yi-Chun Li (Water, Air, & Soil Pollution, 2016)

Low temperature destruction of PCDD/Fs over V2O5-CeO2/TiO2 catalyst with ozone - Ming-feng Yu; Xiao-qing Lin; Mi Yan; Xiao-dong Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Suppression of dioxins by S-N inhibitors in pilot-scale experiments - Ming-Xiu Zhan; Jian-Ying Fu; Tong Chen; Xiao-Qing Lin; Xiao-Dong Li; Jian-Hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Catalytic destruction of PCDD/Fs over vanadium oxide-based catalysts - Ming-feng Yu; Xiao-qing Lin; Xiao-dong Li; Mi Yan; Bayu Prabowo; Wen-wei Li; Tong Chen; Jian-hua Yan (Environmental Science and Pollution Research, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Emission and distribution of PCDD/Fs and CBzs from two co-processing RDF cement plants in China - Tong Chen; Ming-Xiu Zhan; Xiao-qing Lin; Ye-qing Li; Jiang Zhang; Xiao-Dong Li; Jian-hua Yan; Alfons Buekens (Environmental Science and Pollution Research, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Mechanical Analysis of Static Stress Within Fault-Pillars Based on a Voussoir Beam Structure - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Isolation, diversity and acetylcholinesterase inhibitory activity of the culturable endophytic fungi harboured in Huperzia serrata from Jinggang Mountain, China - Ya Wang; Zheng Lai; Xi-Xi Li; Ri-Ming Yan; Zhi-Bin Zhang; Hui-Lin Yang; Du Zhu (World Journal of Microbiology and Biotechnology, 2016)

Roadway Stagger Layout for Effective Control of Gob-Side Rock Bursts in the Longwall Mining of a Thick Coal Seam - Zhen-lei Li; Lin-ming Dou; Wu Cai; Gui-feng Wang; Yan-lu Ding; Yong Kong (Rock Mechanics and Rock Engineering, 2016)

Characterization of Rebound Depolarization in Neurons of the Rat Medial Geniculate Body In Vitro - Xin-Xing Wang; Yan Jin; Hui Sun; Chunlei Ma; Jinsheng Zhang; Ming Wang; Lin Chen (Neuroscience Bulletin, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Characterization of Rebound Depolarization in Neurons of the Rat Medial Geniculate Body In Vitro - Xin-Xing Wang; Yan Jin; Hui Sun; Chunlei Ma; Jinsheng Zhang; Ming Wang; Lin Chen (Neuroscience Bulletin, 2016)

RETRACTED ARTICLE: Effects of Repetitive Transcranial Magnetic Stimulation on Cognitive Impairment in Stroke Patients: A Meta-Analysis - Lei Cao; Rui Zhao; Su Huo; Ju-Bao Du; Lin Liu; Yan-Ming Zhang; Wei-Qun Song (Molecular Neurobiology, 2015)

A new directional query method for polygon dataset in spatial database - Wei Hua Lin; Xiao Jun Tan; Fu Jiang Liu; Yan Yu; Wei Ming Wang (Earth Science Informatics, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

The associations between metals/metalloids concentrations in blood plasma of Hong Kong residents and their seafood diet, smoking habit, body mass index and age - Yan Yan Qin; Clement Kai Man Leung; Che Kit Lin; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

A large-scale breeding experiment and observations on development of Cyanea nozakii (Scyphozoa, Cyaneidae) from fertilized eggs to larval medusae - Chun-sheng Liu; Zhi-meng Zhuang; Si-qing Chen; Jing-ping Yan; Chang-lin Liu; Jian-ming Sun (Hydrobiologia, 2015)

Transcriptome-wide identification of the genes responding to replanting disease in Rehmannia glutinosa L. roots - Yan Hui Yang; Ming Jie Li; Xin Yu Li; Xin Jian Chen; Wen Xiong Lin; Zhong Yi Zhang (Molecular Biology Reports, 2015)

Identification and localized expression of putative K+/H+ antiporter genes in Arabidopsis - Lei Han; Jun Lin Li; Li Wang; Wei Ming Shi; Yan Hua Su (Acta Physiologiae Plantarum, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Gastropulmonary Route of Infection and the Prevalence of Microaspiration in the Elderly Patients with Ventilator-Associated Pneumonia Verified by Molecular Microbiology-GM-PFGE - Qing-hua Liu; Jing Zhang; Dian-jie Lin; Xiao-yan Mou; Li-xian He; Jie-ming Qu; Hua-yin Li; Bi-jie Hu; Ying-min Zhu; Du-ming Zhu; Xiao-dong Gao (Cell Biochemistry and Biophysics, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Stress signaling in response to polycyclic aromatic hydrocarbon exposure in Arabidopsis thaliana involves a nucleoside diphosphate kinase, NDPK-3 - Hong Liu; David Weisman; Ling Tang; Long Tan; Wen-ke Zhang; Zong-hua Wang; Yan-he Huang; Wen-xiong Lin; Xuan-ming Liu; Adán Colón-Carmona (Planta, 2015)

Calreticulin is localized at mitochondria of rat cardiomyocytes and affected by furazolidone - Hu Shan; Jin Wei; Ming Zhang; Lin Lin; Rui Yan; Yanhe Zhu; Rong Zhang (Molecular and Cellular Biochemistry, 2014)

Differences in functional activity between boys with pure oppositional defiant disorder and controls during a response inhibition task: a preliminary study - Yan Zhu; Kui Ying; Ji Wang; Linyan Su; Jingyuan Chen; Fan Lin; Dongyang Cai; Ming Zhou; Daxing Wu; Courtney Guo; Shi Wang (Brain Imaging and Behavior, 2014)

Expansion of regulatory T cells from umbilical cord blood and adult peripheral blood CD4+CD25+ T cells - Syh-Jae Lin; Chun-Hao Lu; Dah-Chin Yan; Pei-Tzu Lee; Hsiu-Shan Hsiao; Ming-Ling Kuo (Immunologic Research, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

Differential Regulation of Lipid Metabolism Genes in the Brain of Acetylcholinesterase Knockout Mice - Huang-Quan Lin; Yan Wang; Kam-Leung Chan; Tsz-Ming Ip; Chi-Cheong David Wan (Journal of Molecular Neuroscience, 2014)

Mapping daily temperature and precipitation in the Qilian Mountains of northwest China - Shou-zhang Peng; Chuan-yan Zhao; Xiao-ping Wang; Zhong-lin Xu; Xing-ming Liu; Hu Hao; Shi-fei Yang (Journal of Mountain Science, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Two new dammarane-type glycosides from Phlomis umbrosa - Ming-Ming Ding; Fu-Lin Yan; Jing Tan; Yi-Xiao Bai; Xiang Wang; Yan-Xia Yang (Natural Product Research, 2014)

A new oleanane-type triterpenoidal saponin from Pulsatilla chinensis - Zhan Shu; Zhong Chen; Yan-li Liu; Wei-feng Zhu; Yu-lin Feng; Qiong-ming Xu; Xiao-ran Li; Shi-lin Yang (Natural Product Research, 2013)

Acid loading stimulates rat glomerular mesangial cells proliferation through Na+–H+ exchanger isoform 1 (NHE1)-dependent pathway - Kun Li; Wei Su; Man Li; Chang-jie Chen; Yong-yu Li; Lin-yun Lai; Ming-min Zhang; Shao-jun Liu; Jakub Fichna; Ai Peng; Chuan-ming Hao; Yong Gu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Characterization and Genome Sequencing of Phage Abp1, a New phiKMV-Like Virus Infecting Multidrug-Resistant Acinetobacter baumannii - Guangtao Huang; Shuai Le; Yizhi Peng; Yan Zhao; Supeng Yin; Lin Zhang; Xinyue Yao; Yinling Tan; Ming Li; Fuquan Hu (Current Microbiology, 2013)

Renin–Angiotensin System Modulates Neurotransmitters in the Paraventricular Nucleus and Contributes to Angiotensin II-Induced Hypertensive Response - Jie Qi; Dong-Mei Zhang; Yu-Ping Suo; Xin-Ai Song; Xiao-Jing Yu; Carrie Elks; Yuan-Xi Lin; Yan-Yan Xu; Wei-Jin Zang; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Construction and analysis of different expression cDNA libraries in Rehmannia glutinosa plants subjected to continuous cropping - Yan Hui Yang; Zhong Yi Zhang; Hua Min Fan; Yi Dan Zhao; Ming Jie Li; Juan Li; Jun Ying Chen; Wen Xiong Lin; Xin Jian Chen (Acta Physiologiae Plantarum, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

A new species of Lophodermium associated with the needle cast of Cathay silver fir - Xiao-Ming Gao; Ying-Ren Lin; Hua-Yan Huang; Cheng-Lin Hou (Mycological Progress, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Orchid fleck virus: an unclassified bipartite, negative-sense RNA plant virus - De Wei Peng; Guo Hua Zheng; Zhi Zhong Zheng; Qing Xuan Tong; Yan Lin Ming (Archives of Virology, 2013)

Thaxtomin A-deficient endophytic Streptomyces sp. enhances plant disease resistance to pathogenic Streptomyces scabies - Lan Lin; Hui Ming Ge; Tong Yan; Yan Hua Qin; Ren Xiang Tan (Planta, 2012)

Development of a substrate-coupled biocatalytic process driven by an NADPH-dependent sorbose reductase from Candida albicans for the asymmetric reduction of ethyl 4-chloro-3-oxobutanoate - Ping Cai; Mingdong An; Lin Xu; Sheng Xu; Ning Hao; Yan Li; Kai Guo; Ming Yan (Biotechnology Letters, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Classical swine fever virus NS5A protein localizes to endoplasmic reticulum and induces oxidative stress in vascular endothelial cells - Lei He; Yan-ming Zhang; Zhi Lin; Wei-wei Li; Jing Wang; He-Lin Li (Virus Genes, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

The mitochondrial genome of the quiet-calling katydids, Xizicus fascipes (Orthoptera: Tettigoniidae: Meconematinae) - MING RU YANG; ZHI JUN ZHOU; YAN LIN CHANG; LE HONG ZHAO (Journal of Genetics, 2012)

Amino Acid Profiles of Bivalve Mollusks from Beibu Gulf, China - De-Wei Chen; Jian Su; Xiao-Ling Liu; Dong-Mei Yan; Ying Lin; Wei-Ming Jiang; Xiao-Han Chen (Journal of Aquatic Food Product Technology, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Pt and Pd in sediments from the Pearl River Estuary, South China: background levels, distribution, and source - Li-feng Zhong; Wen Yan; Jie Li; Xiang-lin Tu; Bao-ming Liu; Zhen Xia (Environmental Science and Pollution Research, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Experimental Pathogenicity of a Clinical Isolate of Trichosporon dermatis in a Murine Model - Ying-Ping Lin; Yan-Ping Yang; Wen-Ming Huang; Yong-Hua Chen; Shun-Fan Li; Yi-Ming Fan (Mycopathologia, 2011)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Enhancing the production of uridine 5′-monophosphate by recombinant Saccharomyces cerevisiae using a whole cell biocatalytic process - Xuelian Yang; Gaoxin Lei; Hanjie Ying; Lin Xu; Ming Yan (World Journal of Microbiology and Biotechnology, 2011)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

Single amino acid residue changes in subsite −1 of levansucrase from Zymomonas mobilis 10232 strongly influence the enzyme activities and products - Shuying Li; Yongliang Yan; Zhengfu Zhou; Haiying Yu; Yuhua Zhan; Wei Zhang; Ming Chen; Wei Lu; Shuzhen Ping; Min Lin (Molecular Biology Reports, 2011)

Do higher resource capture ability and utilization efficiency facilitate the successful invasion of native plants? - Xing-Yan Shen; Shao-Lin Peng; Bao-Ming Chen; Jun-Xiao Pang; Lei-Yi Chen; Hao-Ming Xu; Yu-Ping Hou (Biological Invasions, 2011)

Three new fatty acids from the roots of Boehmeria nivea (L.) Gaudich and their antifungal activities - Qiong-Ming Xu; Yan-Li Liu; Xiao-Ran Li; Xia Li; Shi-Lin Yang (Natural Product Research, 2011)

Inhibition of an invasive plant (Mikania micrantha H.B.K.) by soils of three different forests in lower subtropical China - Yu-Ping Hou; Shao-Lin Peng; Bao-Ming Chen; Guang-Yan Ni (Biological Invasions, 2011)

Eucommia ulmoides Oliv. antagonizes H2O2-induced rat osteoblastic MC3T3-E1 apoptosis by inhibiting expressions of caspases 3, 6, 7, and 9 - Jun Lin; Yi-jing Fan; Christian Mehl; Jia-jun Zhu; Hong Chen; Ling-yan Jin; Jing-hong Xu; Hui-ming Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Dynamic Changes of Heme Oxygenase-1 in the Hippocampus of Rats After Acute Carbon Monoxide Poisoning - Li Guan; Yan-Lin Zhang; Tao Wen; Xi-Fu Wang; Ming-Xia Zhu; Jin-Yuan Zhao (Archives of Environmental Contamination and Toxicology, 2011)

Improvement of an E. coli bioreporter for monitoring trace amounts of phenol by deletion of the inducible σ54-dependent promoter - Zixin Peng; Yongliang Yan; Yuquan Xu; Masahiro Takeo; Haiying Yu; Zhonglin Zhao; Yuhua Zhan; Wei Zhang; Min Lin; Ming Chen (Biotechnology Letters, 2010)

Deformation mechanism and stability evaluation for the left abutment slope of Jinping I hydropower station - Runqiu Huang; Feng Lin; Ming Yan (Bulletin of Engineering Geology and the Environment, 2010)

Effects of exogenous annexin-1 on lipopolysaccharide-induced proliferation and reactive oxygen species production partially through modulation of CRAC channels but independent of NF-κB pathway - Lei-Ming Xu; Sheng-Wei Jin; Xiao-Yan Zhou; Ping Wu; Yong-Sheng Li; Li Zhang; Yuan-Yuan Lin; Ying Chen; Du-Yun Ye (Inflammation Research, 2009)

Benzoate Catabolite Repression of the Phenol Degradation in Acinetobacter calcoaceticus PHEA-2 - Yuhua Zhan; Haiying Yu; Yongliang Yan; Shuzhen Ping; Wei Lu; Wei Zhang; Ming Chen; Min Lin (Current Microbiology, 2009)

Functional analysis of a putative regulatory gene, tadR, involved in aniline degradation in Delftia tsuruhatensis AD9 - Lizhao Geng; Ming Chen; Quanfeng Liang; Wei Liu; Wei Zhang; Shuzhen Ping; Wei Lu; Yongliang Yan; Weiwei Wang; Masahiro Takeo; Min Lin (Archives of Microbiology, 2009)

Effects of the invasive plant Mikania micrantha H.B.K. on soil nitrogen availability through allelopathy in South China - Bao-Ming Chen; Shao-Lin Peng; Guang-Yan Ni (Biological Invasions, 2009)

A novel carbonyl reductase from Pichia stipitis for the production of ethyl (S)-4-chloro-3-hydroxybutanoate - Qi Ye; Ming Yan; Lin Xu; Hou Cao; Zhenjiang Li; Yong Chen; Shuya Li; Hanjie Ying (Biotechnology Letters, 2009)

Genes Involved in the Benzoate Catabolic Pathway in Acinetobacter calcoaceticus PHEA-2 - Yuhua Zhan; Haiying Yu; Yongliang Yan; Ming Chen; Wei Lu; Shuying Li; Zixin Peng; Wei Zhang; Shuzhen Ping; Jin Wang; Min Lin (Current Microbiology, 2008)

A single residue mutation of 5-enoylpyruvylshikimate-3-phosphate synthase in Pseudomonas stutzeri enhances resistance to the herbicide glyphosate - Aimin Liang; Jiying Sha; Wei Lu; Ming Chen; Liang Li; Dan Jin; Yongliang Yan; Jin Wang; Shuzhen Ping; Wei Zhang; Yiding Wang; Min Lin (Biotechnology Letters, 2008)

Involvement of GlnK, a PII protein, in control of nitrogen fixation and ammonia assimilation in Pseudomonas stutzeri A1501 - Sheng He; Ming Chen; Zhihong Xie; Yongliang Yan; Hongquan Li; Ying Fan; Shuzhen Ping; Min Lin; Claudine Elmerich (Archives of Microbiology, 2008)

Solid Substrate–Room Temperature Phosphorimetry for the Determination of Trace Terbutaline Sulfate Based on Its Inhibition Oxidation of Rhodamine 6G by Sodium Periodate - Jia-Ming Liu; Fei Gao; Wen-Yan Gao; Li-Qing Zeng; Xiao-Mei Huang; Zhi-Ming Li; Xiu-Chai Huang; Wei-Nv Lin; Fang-Mei Wang; Chang-Ling Nie (Journal of Fluorescence, 2008)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Using SSR markers to determine the population genetic structure of wild apricot (Prunus armeniaca L.) in the Ily Valley of West China - He Tian-Ming; Chen Xue-Sen; Xu Zheng; Gao Jiang-Sheng; Lin Pei-Jun; Liu Wen; Liang Qing; Wu Yan (Genetic Resources and Crop Evolution, 2007)

Reduction in the in vitro expression of Brain–Pancreas Relative Protein by oxygen and glucose-deprivation - Yan-Hua Lin; Ai-Hua Liu; Yan Pan; Christel Westenbroek; Gert J Ter Horst; He-Ming Yu; Xue-Jun Li (Molecular and Cellular Biochemistry, 2007)

Studies on characteristics of nanostructure of N-TiO2 thin films and photo-bactericidal action - Ming-fang Xu; Shan Lin; Xin-man Chen; Yan-zhi Peng (Journal of Zhejiang University-SCIENCE B, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Molecular analysis of increased iron status in moderately exercised rats - Yu Qian Liu; Xiang Lin Duan; Yan Zhong Chang; Hai Tao Wang; Zhong Ming Qian (Molecular and Cellular Biochemistry, 2006)

Cloning and Characterization of the First Cnidarian ADP-Ribosylation Factor, and Its Involvement in the Aiptasia-Symbiodinum Endosymbiosis - Ming-Chyuan Chen; Ying-Min Cheng; Li-Hsueh Wang; Chorng-Horng Lin; Xing-Yan Huang; Ming-Chin Liu; Ping-Jyun Sung; Lee-Shing Fang (Marine Biotechnology, 2004)

Conversion of an obligate autotrophic bacteria to heterotrophic growth: expression of a heterogeneous phosphofructokinase gene in the chemolithotroph Acidithiobacillus thiooxidans - Ke Li Tian; Jian Qun Lin; Xiang Mei Liu; Ying Liu; Chang Kai Zhang; Wang Ming Yan (Biotechnology Letters, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Conversion of trypsin into a selenium-containing enzyme by using chemical mutation - Jun-Qiu Liu; Ming-Shou Jiang; Gui-Min Luo; Gang-Lin Yan; Jia-Cong Shen (Biotechnology Letters, 1998)